Prove:

If a positive integer n is not prime, then 2^(n)-1 is not prime.

If n is not prime, then it factors into n = a*b. Use the identityx^(b) = (x-1)(x^(b-1) + x^(b-2) + ...+ x + 1) and substitute x = 2^(a).

Printable View

- Oct 20th 2008, 09:57 PMnoles2188Need help doing a proof
Prove:

If a positive integer n is not prime, then 2^(n)-1 is not prime.

If n is not prime, then it factors into n = a*b. Use the identityx^(b) = (*x*-1)(*x*^(b-1) + x^(b-2) + ...+ x + 1) and substitute x = 2^(a).

- Oct 21st 2008, 01:25 AMOpalg